AL-HAQIQOH WAL MAJAZ ‘ENDA AL-WUSHULIIN WAL-LUGHOWIIN - Lubis, Torkis (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2008)
The issue of words and meanings is a major topic in linguistics, and Arabic is no exception. The discourse between the true meaning and majazi (figurative) meaning is among the most fascinating areas of study for both linguists (lughawi) and theologians (ushuli). This paper focuses on the differing views between linguists and theologians regarding the ultimate meaning (hakikat) and the figurative meaning (majazi). Theologians categorize hakikat into lughawi (linguistic) and shar’i (religious/legal), while linguists distinguish between wadh’i (contextual/conventional) and ‘urfy (customary usage, which includes ‘aam for general meaning and khas for specific meaning). Similarly, the majazi meaning is further divided into lughawi (linguistic), ‘urfy (customary), and shar’i (religious/legal) meanings. The implications of this finding highlight the nuanced approach both disciplines take in understanding and interpreting language, reflecting their distinct objectives. Linguists focus on how meaning evolves within social and cultural contexts, prioritizing conventions and linguistic utility, while theologians aim to interpret meanings within religious texts, emphasizing divine intent and doctrinal coherence. This distinction underscores the interdisciplinary nature of language studies in Arabic and demonstrates how the interplay of linguistic and theological perspectives enriches the broader understanding of semantics and hermeneutics. Moreover, these findings offer valuable insights for modern linguistic and theological debates, particularly in navigating textual interpretation in contemporary contexts.